Manufacturing of high toughness hydroxyapatite produced by wet chemical method - Tolouei, R.; Singh, R.; Tan, C.Y.; Satgunam, M.; Amiriyan, M. (2012)
Hydroxyapatite (HA) is among the leading ceramic materials for hard tissue replacement implants. Despite the excellent bioactivity of HA, low toughness has limited the application of these materials to non-load bearing areas. The sinterability of nanocrystalline hydroxyapatite (HA) powder via new heating profile for conventional pressureless sintering was studied. The starting nanocrystalline HA powder was synthesized by wet chemical precipitation method. After uniaxial pressing followed by isostatic pressing, HA powder compacts are sintered over the temperature range of 1000 degrees C to 1300 degrees C. Different holding time of 1 minute and 120 minutes was applied as a heating profile of HA samples. The results revealed that new heating profile was effective in producing a HA body with high density of 98 when sintered at 1200 degrees C. Subsequently, mechanical properties such as fracture toughness and hardness, of HA compacts increased with decrease in grain size. HA showed the highest hardness of 9.51 GPa and fracture toughness of 1.41 MPa.m1/2 when sintered at 1100 degrees C. XRD analysis indicated that decomposition of HA phase during sintering at high temperatures do not occur. Short holding time leads to finer microstructure of HA and subsequently better mechanical properties.